2015
DOI: 10.1038/ismej.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community successional patterns in beach sands impacted by the Deepwater Horizon oil spill

Abstract: Although petroleum hydrocarbons discharged from the Deepwater Horizon (DWH) blowout were shown to have a pronounced impact on indigenous microbial communities in the Gulf of Mexico, effects on nearshore or coastal ecosystems remain understudied. This study investigated the successional patterns of functional and taxonomic diversity for over 1 year after the DWH oil was deposited on Pensacola Beach sands (FL, USA), using metagenomic and 16S rRNA gene amplicon techniques. Gamma- and Alphaproteobacteria were enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
133
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 66 publications
(73 reference statements)
14
133
3
Order By: Relevance
“…Metagenome and genome sequences were trimmed using SolexaQA (59), with a Phred score cutoff (-h) of 20 and a minimum fragment length of 50 bp, as described previously (60). Only paired reads with both sisters longer than 50 bp after trimming were used further (Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenome and genome sequences were trimmed using SolexaQA (59), with a Phred score cutoff (-h) of 20 and a minimum fragment length of 50 bp, as described previously (60). Only paired reads with both sisters longer than 50 bp after trimming were used further (Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…The relative abundances of isolates and genes were calculated as the ratio of the total length of all reads mapping on a reference isolate genome or gene sequence divided by the total length of the reference sequence (ϫ coverage or sequencing depth). To calculate the genome equivalent for each gene/function, i.e., the fraction of total cells containing the gene, an in-house ruby script was used, essentially as described previously (60). Briefly, the script is used to detect and extract reads containing any of 91 essential protein-coding genes (universally conserved single-copy) (75) from the Genome Property database (entry ID, GenProp0799, named "bacterial core gene set, exactly 1 per genome") (76).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, metagenome sequencing (i.e., random sequencing of total community DNA extracts) has recently been used to examine the functional network of complex microbial communities (28,29). In spite of the rise of infections by opportunistic premise plumbing pathogens, relatively few studies have assessed the diversity of biofilms growing in DWDS at the metagenome level, especially in health care units (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…Similar kinds of studies have been reported for microbial capability exploiting oil and its derivatives as a source of carbon and energy 32,33 . Recently, Rodriguez-R et al 34 reported that the successional patterns of microbial communities respond to crude oil agitation, supporting the specialization disturbance hypothesis during degradation.…”
Section: Discussionmentioning
confidence: 88%